Pengaruh Tanaman Lidah Mertua (Sansevieria trifasciata) terhadap Penurunan Kadar Pb (Plumbum) di Udara - Siti Nurjannah; Sri Muryani; Adib Suyanto (Poltekkes Kemenkes Yogyakarta, 2018)
Pb pollution is harmful for human health. The monitoring results of Pb air ambient measurementby the Environment Agency of Yogyakarta City in 2016 showed that at five measurement points the Pb exceeded the threshold regulated by the Decree of Yogyakarta Province Governor No. 153 in 2002, i.e. 2 ?g/m3 secondary quality standard 1,500 ?g/m3. The purpose of this study was to know the effect of Sansevieria trifasciata on decreasing Pb levels in air. This research was a quasi-experiment with control time series design. There were three time exposure variation of Sansevieria trifasciata, namely 30 minutes, 60 minutes and 90 minutes, in five replications. The research employed special designed glass box to input the pollutant emission from vehicle. The study results show that 30 minute exposure of Sansevieria trifasciata can decrease Pb from pretest measurement of 829,64 ?g/m3to 269,6 ?g/m3 (30,56 %), 60 minutes exposure decreased to 346,22 ?g/m3 (41,70 %) and 90 minutes ex-posure decreased to 368,16 ?g/m3 (44,63 %).